Preparation of active antibacterial biomaterials based on sparfloxacin, enrofloxacin, and lomefloxacin deposited on polyethylene. Issue 15 (22nd December 2017) - Ozaltin, Kadir; Lehocky, Marian; Humpolicek, Petr; Vesela, Daniela; Mozetic, Miran; Novak, Igor; Saha, Petr
ABSTRACT: Bacterial contamination is one of the biggest drawbacks of implanted biomaterials, which may cause nosocomial infection. Avoiding bacterial adhesion onto the biomaterial surface by preparing active antibacterial biomaterials is an accurate solution. In this study, three of the fluoroquinolones: sparfloxacin, enrofloxacin, and lomefloxacin were selected due to their broad bactericidal effect and immobilized onto low‐density polyethylene surface at two different pH values (pH 3 and pH 6), after tailoring the surface by plasma treatment followed by grafting of polymer brush of N ‐allylmethylamine. Surface wettability test and morphological investigations were carried out by water contact angle measurement and scanning electron microscopy analysis, respectively. Chemical characterizations were carried out by Fourier transform infrared spectra and X‐ray photoelectron spectroscopy. Antibacterial activity was checked against Staphylococcus aureus and Escherichia coli strains and results revealed that prepared surfaces were more effective against E. coli than S. aureus especially those prepared at pH 6. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46174. Abstract :